Changes in Salmon (Oncorhynchus keta) Flesh Quality Following Ultra‐High Pressure Treatment and 30 d of Chilled Storage. Issue 1 (17th December 2014) - Park, Dae‐Hun; Jung, Jong‐Gi; Jung, Bo‐Ram; Kim, Gyeyeop; Lee, Honggyun; Kim, Hyeon‐A.; Bang, Mi‐Ae
Abstract The approximately 1.5 million tons of salmon traded in 31 countries in 2008 provides clear evidence that salmon is a popular food source throughout the world. There are many methods for the preservation of salmon flesh, such as vacuum‐packaging, smoking, and freezing. Ultra‐high pressure (UHP) does not require heat, preserves the quality of salmon flesh, and allows for an increase in the chilled storage period. In this study, the quality of salmon flesh was assessed after exposure to UHP (200, 400, or 600 MPa compared with no UHP) and 30 d of storage at 4 °C. Salmon flesh quality analyses included the degree of changes in the interspacing of muscle bundles, color, texture profiles (hardness, chewiness, cohesiveness, and elasticity), and microbial growth. The use of UHP (>400 MPa) improved the color, hardness, and chewiness of the flesh. Study results suggested that the application of UHP (≥400 MPa) may be useful in preserving salmon flesh, and could be used by the salmon aquaculture and distribution industries.